Temporary reduction of sugar levels in diabetes mellitus sufferers on the effect of diabetes mellitus exercises at Salewangan Maros Hospital, Maros Regency - Yusnayanti, Cici; Manuntungi, Andi Ernawati; Suabey, Suningsih; Ruben, Sethiana Dewi; Wijayanti, Lumastari Ajeng; Ganoko, Marwan Ahmad; Rahmat, Rezqiqah Aulia (Institute of Computer Science (IOCS), 2024)
One of the causes of Diabetes Mellitus is a lack of exercise or physical activity. Glycogen or fat reserves will accumulate enough in the body if a person does not do physical activity or exercise. The aim of this research is to determine the effect of diabetes mellitus exercise on reducing sugar levels over time in diabetes mellitus sufferers. This research method is pre-experimental with a one group pre-post test design approach. The sampling technique used was total sampling with data analysis using the data normality test. The results of this study showed differences in blood sugar levels before and after doing diabetes exercises. After doing diabetes exercises, blood sugar levels drop. The decrease in blood sugar levels varied from one respondent to another. This indicates that exercise has a significant influence on reducing blood sugar levels in Diabetes Mellitus sufferers.